DESA CERDAS: MEMBERDAYAKAN MASYARAKAT MELALUI KEGIATAN MENGGAGAS SERAMBI LITERASI DI DESA KANJILO KECAMATAN BAROMBONG KABUPATEN GOWA - untung, untung (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
This writing aims to understand the concept of the program "Smart Village: Empowering Communities Through Activities to Initiate Literacy Verandas. The writing method used is identifying village potential and community problems, conducting FGDs with partner teams and institutions, designing, implementing and evaluating programs. Smart Village is one of the programs of PPK Ormawa Community Lab PLS FIP UNM as a literacy forum for the Kanjilo village community. The smart village provides various literacy corners in six hamlets, Kanjilo village. Through an innovative and participatory approach, the "Smart Village" program is committed to not only providing access to information, but also empowering people to become independent learners. By involving the community in planning and implementing activities, we hope to encourage active participation and a sense of ownership of this program. Thus, the "Smart Village" not only functions as a place of learning, but also as a community center that supports sustainable education and literacy